Venous Thromboembolism During Chemotherapy for Testicular Cancer: A Population-Based Study. Issue 10 (October 2020) - Robinson, A.G.; Wei, X.; Karim, S.; Raphael, M.J.; Bedard, P.L.; Booth, C.M.
Abstract: Aims: Venous thromboembolism (VTE) is a potential complication among germ cell tumour patients. We evaluated the incidence rate, timing and factors associated with VTE among patients with germ cell cancer in routine practice. Materials and methods: The Ontario Cancer Registry was linked to electronic records of treatment to identify all cases of testicular cancer treated in Ontario during 2000–2010. Administrative databases were used to identify VTE in the 3 months before and 5 years after orchiectomy. We explored patient-, disease- and treatment-related factors associated with VTE among all patients as well as those with detailed chemotherapy records available. Results: During 2000–2010, 2650 patients underwent orchiectomy for testicular cancer; among this cohort, 920 (33%) received chemotherapy. The VTE rate was 8% (69/920) among patients treated with chemotherapy and 0.6% (11/1730) among those without chemotherapy. Among the patients treated with chemotherapy who had VTE, 13% (9/69) occurred in the month before starting chemotherapy, 62% (42/69) in the first 3 months after starting and 25% thereafter. For patients who received three and four cycles, VTE rates were 8% (21/258) and 16% (19/121), respectively. In adjusted analyses, the only factor independently associated with VTE was increasing number of cycles (odds ratio 3.91 for four cycles, odds ratio 1.63 for three cycles ( P  = 0.022) compared with one to two cycles). Conclusion: This population-based study confirms findings from institutional case series regarding the high rate of VTE among patients with germ cell tumours treated with chemotherapy. Future studies should evaluate the extent to which VTE prophylactic strategies might mitigate this risk. Highlights: A population-based assessment of thromboembolic risk in testes cancer patients was performed in Ontario, Canada. VTE rate for patients receiving 4 cycles of chemotherapy was 16%, with most after starting chemotherapy and within 4 months. These rates are above that where thromboprophylaxis is typically considered.